2020
DOI: 10.1089/gtmb.2020.0201
|View full text |Cite
|
Sign up to set email alerts
|

Association of ABCB1 and CYP450 Gene Polymorphisms and their DNA Methylation Status with Steroid-Induced Osteonecrosis of the Femoral Head in the Chinese Population

Abstract: Osteonecrosis of the femoral head (ONFH) is a severe pathological state with multiple etiologies. Steroid hormone metabolism-related genes play an important role in ONFH. The aim of this study was to investigate the relationships between polymorphisms of the drug-metabolizing enzyme gene, cytochrome P450 (CYP450), and the drug transporter gene, ATP-binding cassette subfamily B member 1 (ABCB1), as well as their DNA methylation status with the pathogenesis of steroid-induced ONFH. Methods: In this case-control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…There were no healthy people receiving steroid treatment. The control group included healthy subjects who were widely used in most of the studies, rather than patients receiving steroid treatment with other conditions [ 27 ]. The reason is that even if the patients with SLE and ONFH, which accounted for the highest proportion of the disease, were taken as the control group, the resulting statistical conclusion could only prove the difference between the two diseases.…”
Section: Discussionmentioning
confidence: 99%
“…There were no healthy people receiving steroid treatment. The control group included healthy subjects who were widely used in most of the studies, rather than patients receiving steroid treatment with other conditions [ 27 ]. The reason is that even if the patients with SLE and ONFH, which accounted for the highest proportion of the disease, were taken as the control group, the resulting statistical conclusion could only prove the difference between the two diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Other SNPs with an impact on steroid-induced osteonecrosis have been demonstrated for cytochrome P450 and associated with lower risk [ 25 ], whereas different IL1B polymorphisms influence the risk for steroid-induced osteonecrosis [ 26 ]. Metalloproteinase 2, 8, and 10 polymorphisms contribute to susceptibility [ 27 , 28 ], as RETN (coding for resistin, an adipokine involved in metabolic disorders) and ApoA 5 and APOE (involved in lipid metabolism) SNP [ [29] , [30] , [31] ].…”
Section: Pathogenesismentioning
confidence: 99%
“… Gene Risk Ref. ATP-binding cassette subfamily B member 1 (ABCB1) Reduced [ 24 ] Cytochrome P450 Reduced [ 25 ] IL1B Increased or reduced [ 26 ] Metalloproteinase 2, 8, and 10 Increased [ 27 , 28 ] Metalloproteinase 9 Reduced [ 32 ] RETN Increased [ 29 ] APOA5 Increased [ 30 ] APOE Increased [ 31 ] TIMP4 Reduced [ 33 ] PAI-1 Increased [ 34 ] LncRNA LINC-PINT Increased [ 35 ] VEGF Increased [ 13 ] NO Increased [ 13 ] …”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, emerging lines of evidence have suggested genetic factors and hereditary forms play a pivotal role in ONFH development [ 5 ]. For example, NOS3 , IL-1B , ABCB1 and CYP450 single nucleotide polymorphisms (SNPs) were closely related to the susceptibility of ONFH [ 6 8 ]. However, many variants contributed to ONFH remain to be identified.…”
Section: Introductionmentioning
confidence: 99%